2003
DOI: 10.1017/s0031182002002925
|View full text |Cite
|
Sign up to set email alerts
|

Effects of experimental Schistocephalus solidus infections on growth, morphology and sexual development of female three-spined sticklebacks, Gasterosteus aculeatus

Abstract: The use of naturally infected hosts in studies attempting to identify parasite-induced changes in host biology is problematical because it does not eliminate the possibility that infection may be a consequence, rather than a cause, of host trait variation. In addition, uncontrolled concomitant infections may confound results. In this study we experimentally infected individual laboratory-bred female three-spined sticklebacks Gasterosteus aculeatus L. with the pseudophyllidean cestode Schistocephalus solidus [M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 34 publications
1
75
1
Order By: Relevance
“…Similarly, it seems evident that some phenotypic traits make some individuals more susceptible to parasitic infections. Currently, the diVerential susceptibility between hosts and parasite is rarely considered, principally because most studies on the eVects of parasites on host phenotype experimentally infect hosts using individual exposure to parasites (e.g., Barber and Svensson 2003;Blair and Webster 2007). Such a design should be altered to exploit any natural pre-existing diVerences in the susceptibility of hosts and for disentangling causes and consequences in host-parasite interactions (Poulin 1998;Barber et al 2000).…”
Section: Weakly Infected Host Heavily Infected Hostmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it seems evident that some phenotypic traits make some individuals more susceptible to parasitic infections. Currently, the diVerential susceptibility between hosts and parasite is rarely considered, principally because most studies on the eVects of parasites on host phenotype experimentally infect hosts using individual exposure to parasites (e.g., Barber and Svensson 2003;Blair and Webster 2007). Such a design should be altered to exploit any natural pre-existing diVerences in the susceptibility of hosts and for disentangling causes and consequences in host-parasite interactions (Poulin 1998;Barber et al 2000).…”
Section: Weakly Infected Host Heavily Infected Hostmentioning
confidence: 99%
“…Currently, most studies assume that observed variation in the host phenotype population is a consequence of parasite infection (e.g., Lello et al 2005;Holmstad et al 2006;Wood et al 2007). Otherwise, the possibility that the host phenotype can cause diVerent patterns of parasite infection is reduced by experimentally infecting the hosts or by removing parasites from infected hosts (e.g., Albon et al 2002;Barber and Svensson 2003;Seivwright et al 2005;Schultz et al 2006;Blair and Webster 2007). Very few tests have yet been developed to explore the possibility that both causes and consequences may intervene, having reciprocal eVects in underlying the relationship between parasite infection and phenotypic variation within the host population (but see Barber 2005;Bourque et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Because the proportion of S. solidus successfully establishing in host fish after experimental infection is often low (e.g., Arnott et al 2000), the size of the S. solidus-exposed group was increased relative to the number of placebo-exposed controls, and exposed fish were fed multiple infective parasites. At a size of~20 mm (~0.15 g), 20 sticklebacks were each fed copepods (Cyclops strenuus) containing a total of five infective (i.e., cercomer-bearing; Smyth 1994) S. solidus procercoids (see Smyth 1994 andBarber andSvensson 2003 for details of in vitro parasite culture and exposure protocols). Sixteen placebo-exposed control sticklebacks were fed noninfected copepods.…”
Section: Experimental Infectionsmentioning
confidence: 99%
“…All fish were then fed to satiation for a further 6 weeks to allow any compensatory response in weight, length, and condition of the previously food-deprived fish to occur. At weekly intervals, each fish was weighed (to 0.001 g) and digitally photographed from above to allow length measurements (to 0.1 mm) to be made using computerised image analysis (Barber and Svensson 2003). Fish were not anaesthetized prior to being weighed because of concerns over behavioural and appetite effects of repeated anaesthesia and the potential for an interaction with infection status.…”
Section: Feeding Regimesmentioning
confidence: 99%
See 1 more Smart Citation